The Role of Women Village Heads in Decision Making Process in Lembung Timur Village - Nur Inna Alfiyah; Dwi Listia Rika Tini (Journal of Local Government Issues (LOGOS), 2021)
The election of a female village head in Lembung Timur is part of the maturity of the village community of Lembung Timur in seeing the meaning of gender equality in village leadership concerning leadership, especially in the decision-making process. Is it true that the appearance of a female village head to lead the village will be part of the better or more effective village leadership, which will lead to the decision-making process? This study aims to describe the role of female village heads in the decision-making process in Lembung Timur village, Lenteng district. The research method uses descriptive qualitative methods by utilizing qualitative data with descriptive elaboration. This study shows that, mainly in the decision-making process, Mrs. Faizah, as the village head in carrying out her role (manifest function), is only limited to the data collection stage. It can be said that Faizah has carried out her manifest function effectively because, from each stage of the decision-making process, she was done independently. The constraints faced are the lack of ability and experience and the occurrence of gender bias. Qualitatively, this study shows that the latent role or function of women's leadership in decision-making is not practical because the latent function performed in each decision-making process is played by Faizah's parents, namely Mr. Abdul Latif. Therefore, it is needed relating to the ability, skill, courage in playing the latent function for female village heads to break the hegemony of decision-making control by Mrs. Faizah's parents.